2003
DOI: 10.1063/1.1542875
|View full text |Cite
|
Sign up to set email alerts
|

Negative Fukui functions: New insights based on electronegativity equalization

Abstract: Fukui functions have been calculated for large numbers of organic molecules, and were found to always be positive. Numeric and algebraic considerations allowed the identification of several boundary conditions for negative values for Fukui functions. Negative Fukui functions are found to be very unlikely, except when very short interatomic distances are present. Recent hypotheses concerning the occurrence of negative Fukui functions are strongly supported by the present approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 31 publications
0
77
0
1
Order By: Relevance
“…In fact, Roy et al [34][35][36][37][38] have shown that the latter is more reliable than MPA for calculating local reactivity descriptors and also produces nonnegative condensed Fukui function values. A lot of other work on nonnegative Fukui functions has been reported, [39][40][41] and it can be concluded that the Fukui function itself can be negative, although condensed Fukui functions cannot be negative, except in certain cases.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…In fact, Roy et al [34][35][36][37][38] have shown that the latter is more reliable than MPA for calculating local reactivity descriptors and also produces nonnegative condensed Fukui function values. A lot of other work on nonnegative Fukui functions has been reported, [39][40][41] and it can be concluded that the Fukui function itself can be negative, although condensed Fukui functions cannot be negative, except in certain cases.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…Chemical reactivity is often interpreted in terms of the FMO, even though this is not always appropriate. There is a continuing interest in negative Fukui functions [14][15][16][17][18][19][20][21][22], and especially how they can be rationalized, and whether they have chemical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Calculated as well as available experimental hardness data g ¼ I À A are also given in Table I. have not yet been demonstrated for a coherent collection of species [25]. Results of this present work are shown in Figures 1-4.…”
Section: Resultsmentioning
confidence: 83%